Early decisions about breast cancer treatment: perspectives from women and family members - Wan Mamat, Wan Hasliza; Jarrett, Nikki; Hairulisa@Mohd Hairi, Nur Alia; Ahmad, Norfadzilah; Atan, Ashikin; Lund, Susi (2022)
Conventional or hospital treatment such as surgery, chemotherapy or radiotherapy is widely recommended by health care providers for treating breast cancer. However, there is an inadequate understanding of early decision about conventional treatment in Malaysia. This study aimed to explore the early decision about breast cancer treatment among the women and their family members. Purposive and snowball sampling were applied, and 28 participants were recruited in this study. The participants took part in in-depth, face-to-face, and audio-recorded one-time interviews. All of the interviews were subsequently transcribed verbatim and analysed using narrative analysis. Two themes were identified about early decision making about breast cancer treatment: 1) Women and family members who accepted conventional treatment immediately and 2) Women and family members who refused immediate conventional treatment. This study discovered that some women agreed to undergo conventional treatment immediately while others were refused. Healthcare staffs can support women who refused the treatment for breast cancer by educating them regarding the conventional treatment. This can be achieved by proving accurate knowledge about treatment, addressing fears related to treatment, emotional support, and by encouraging open communication about the reasons for refused conventional treatment.